Genesis and Role of Madhesh Movement on state-restructuring in Nepal - Chaudhary, Deepak (Technium Social Sciences Journal, 2020)
The study aims to explore the genesis and the role of the Madhesh movement on state-restructuring in Nepal as well as challenges. This social movement erupted in January 2007 in the Tarai/Madhesh (southern plain terrain) region of Nepal after the issues of federalism and proportional representation were not included in the Interim Constitution. The data collection of this empirically-based study was carried out through In-depth interviews with participants (politicians, journalists, and ordinary people) of the movement, and direct observation. The Madheshi community as the excluded community in Nepal seemed to have angered against state-sponsored discrimination and exclusion that had been occurring for centuries. Madheshis were treated as non-Nepali; though the history of Nepal’s Tarai/Madhesh has been old. The movement was spontaneous to a large extent against the state’s prejudices and discriminations. This movement brought the changes, promoting social justice and equality in essence, and Madheshis / minorities’ rights and inclusion in particular. As a result, the number of electoral constituencies was increased as it reached 120 in Tarai/Madhesh while it was 80 only; the representation of Madheshi and other minorities in the political arena reached 35 % and more, while it was 20% only. The main output of this movement was that it contributed to ensuring the principle of inclusion and federalism as a political system.